PENGARUH MODERNISASI SISTEM ADMINISTRASI DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK - Agustini Eka Pratiwi W., Putu; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2016)
Tax administration is a priority of tax reform. Indonesian state to modernize the tax administration system in order to enhance domestic revenue from the tax sector. Increased tax revenues indicate increased taxpayer compliance in performing their tax obligations. Tax penalty is a law enforcement tool so that taxpayers can fulfill all taxation obligations. The purpose of this study was to determine the influence of modernization of system administration and tax penalties on taxpayer compliance. Location of the research conducted in KPP Pratama Denpasar Timur and population used in this study is an WP OP effective in KPP Pratama Denpasar Timur. 100 people used a sample of which is determined using accidental sampling method. The research data come from questionnaires distributed to respondents with multiple linear regression analysis as data analysis techniques. Results of the analysis reveal any variable positive influence organizational structure, organizational procedures, organizational strategy, organizational culture and tax penalties on taxpayer compliance in KPP Pratama Denpasar Timur.
Keywords: modernization of the administrative system; tax penalty; taxpayer compliance